Advances in accounting education teaching and curriculum innovations. Vol. 6 - Ketz, J. Edward; Schwartz, Bill N. (Advances in accounting education : teaching and curriculum innovations,, 2004)
Advances in Accounting Education is a refereed, academic research annual whose purpose is to help meet the needs of faculty members interested in ways to improve their classroom instruction. We publish thoughtful, well-developed articles that are readable, relevant and reliable. Articles may be either empirical or non-empirical. They emphasize pedagogy, i.e., explaining how faculty members can improve their teaching methods or how accounting units can improve their curricula/programs.